Dokumentasi budaya Baso (tutur sapa kekeluargaan) etnis Pesisir Kota Sibolga, Sumatera Utara - Panggabean, Lailan Saumi; Rizal, Edwin; Kusnandar, Kusnandar (Faculty of Communication, Padjadjaran University, 2024)
Indonesia has a diverse cultural heritage, including the Baso Culture in Coastal Sibolga, North Sumatra. This culture, orally passed down since ancient times, is at risk of being lost due to minimal documentation. Baso reflects close relationships, especially with blood relatives. The family system of the Sibolga Coastal ethnicity follows the paternal lineage, and Baso terms are adapted to the Coastal Language influenced by Minang, Malay, and Batak languages. This research aims to document the Baso Culture of the Sibolga Coastal ethnicity, which currently has minimal information. The study uses library science with a focus on cultural documentation. The methods employed are action research and Participatory Action Research (PAR), with data collection techniques including observation, interviews, and document analysis. The research involves observations to study social behavior and meaning, interviews to deepen information, and data analysis based on references to strengthen the received information. YFKK (Yayasan Forum Komunitas Kreatif) Sibolga Tapanuli Tengah and local cultural experts are involved in the research as part of the PAR approach. The results show that Baso Culture is a way of speaking that reflects the closeness of relationships and a person's position in kinship. The researchers categorized the variations of greetings in Baso into six categories: nuclear family, paternal family, maternal family, male in-laws, female in-laws, and general greetings. Baso Culture is still practiced by the Sibolga Coastal community, but it needs preservation. Preservation efforts are made by documenting it as Instagram content through the accounts of Yayasan Forum Komunitas Kreatif (@tutur.runduk) and the researcher (@lai_bookshelf). This documentation is expected to enrich information and support cultural learning for future generations.